KINERJA LEMBAGA PERKREDITAN DESA (LPD) BERBASIS BALANCED SCORECARD DI KECAMATAN KERAMBITAN-TABANAN - Ni Made Suherawati (Journal of Applied Management Studies, 2021)
The purpose of this study was to determine the performance of LPD in Kerambitan District from a financial perspective, a customer perspective, an internal business process perspective and a growth and learning perspective. This research is a descriptive quantitative research in which it provides an explanation related to the performance measurement of the Village Credit Institution (LPD) of Kerambitan District by using the Balanced Scorecard performance measurement approach. The results of this study are the average ROA ratio of LPDs in Kerambitan District for 3 (three) years, namely 2017, 2018, 2019 is 2.60% and is categorized as healthy. The average BOPO ratio is 81.38% and is categorized as healthy. The average LDR ratio is 77.37% and is categorized as healthy. It can be seen that the LPD in Kerambitan District has good management capabilities in generating profits from the total assets owned, can perform cost efficiency from the income generated and show increased liquidity capabilities. From the customer perspective, LPD performance in Kerambitan District is assessed based on customer assessments with five indicators, namely the completeness of LPD facilities, LPD employee service, LPD employee alertness, security assurance, and care. sophisticated equipment, forms are not provided and customers still have difficulty in filling out forms, long waiting times in service, and there is no special place for customer complaints. The performance of LPD in Kerambitan District, Tabanan from the customer perspective is of good quality, which is 90.4 percent because the proportion of positive statements is higher than 60 percent. From an internal business perspective, an assessment of the LPD product innovation process is carried out in the District of Kerambitan Tabanan. Of the 12 LPDs in Kerambitan District, there are 7 LPDs that have not innovated their products and 5 LPDs that have innovated their products in the 2017-2019 period. The performance of LPDs in Kerambitan District is still not said to be good, this is because LPDs have not innovated or developed with their products in the last 3 year period, namely 2017- 2019. From the perspective of growth and learning, LPD performance in Kerambitan District is assessed based on the assessment of its employees with four indicators, namely awards given, employee commitment, relationships with colleagues and facilities provided by LPD are of good quality, which is 90.96 percent because the proportion of statements positive is higher than 60 percent. LPD employees in Kerambitan Sub-district, Tabanan were satisfied in all the items measured. These results indicate that the LPDs in Kerambitan Sub-district have managed and developed employees well which are able to improve their work abilities.